Patterns Of Drug Use In Patients With Knee Osteoarthritis At The Bina Sehat Jember Hospital - Desie Dwi Wisudanti; Firman Pratama Andraputra; Muhammad Ali Shodikin (Universitas Muhammadiyah Malang, 2022)
Osteoarthritis is a degenerative disease characterized by progressive damage to joint cartilage. The prevalence of osteoarthritis will continue to increase and continue as the population and age increase. Cases of knee osteoarthritis are more common than other types of osteoarthritis. The high prevalence of osteoarthritis will have implications for the high treatment regimen given to patients. Irrational use of drugs can lead to drug-related problems (DRPs). This study used a descriptive design. The sample in this study were knee osteoarthritis patients at the Bina Sehat Jember Hospital. The sampling technique used is purposive sampling. The data in this study used secondary data from patient medical records for the period January 2020 - April 2021. A total of 3 knee osteoarthritis patients have the potential to experience drug-related problems in the drug interaction category.